Association between the systemic immune-inflammatory index and the immune response after hepatitis B vaccination: a cross-sectional analysis of NHANES data - Hu, Jiayan; Huang, Kaiyue; Zou, Hede; Li, Junxiang (Frontiers in Public Health, 2025)
AimOur research aimed to investigate the relationship between the systemic immune-inflammatory index (SII) and the immunological response to hepatitis B vaccination.MethodsWe collected data from the National Health and Nutrition Examination Survey database from 2007 to 2018. To examine the association between the SII and immunological response, we conducted weighted multiple regression analysis and subgroup analysis. Furthermore, we utilized restricted cubic splines (RCSs) to analyze the linear relationship between the two variables.ResultsIn our study, we included a total of 6,123 patients, of whom 2,770 tested positive for hepatitis B antibodies. Multivariate logistic regression analysis indicated that, after controlling for all measured factors, a high level of the SII was inversely associated with the presence of antibodies following three doses of the hepatitis B vaccine (OR = 0.8661, 95% CI = 0.7577–0.9899, p = 0.035). Subgroup analysis and interaction testing revealed that sex, age, body mass index, diabetes, and other factors did not significantly influence this negative association (P for interaction >0.05). Additionally, the RCS model revealed no non-linear relationship between the SII and the immune response to the hepatitis B vaccine (p > 0.05). Notably, antibody expression significantly decreased as the SII increased beyond the threshold of 448.3.ConclusionThis cross-sectional study revealed a strong association between low antibody production following hepatitis B vaccination and the SII. However, this cross-sectional study could not establish a causal relationship between the two variables. Therefore, further experimental verification is necessary to confirm the correlation observed in our study.